Nanomaterials in Extreme Environments Fundamentals and Applications - Andrievski, Rostislav; Khatchoyan, Arsen (Springer Series in Materials Science, 2016)
This book focuses on the behaviour of nanomaterials under extreme conditions of high temperature, irradiation by electron/ions and neutrons as well as in mechanical and corrosion extremes. The theoretical approaches and modeling are presented with numerous results of experimental studies. Different processing methods of extreme-tolerant nanomaterials are described. Many application examples from high-temperature technique, nuclear reactors of new generations, aerospace industry, chemical and general engineering, sensor facility, power engineering, electronics, catalysis and medical preparations are also contained. Some unresolved problems are emphasized.